Conceptual and systematic design approach for XML document warehouses - Nassis, Vicky; Rajugan, Rajagopal; Dillon, Tharam S.; Rahayau, Wenny (Information Science Reference, 2008)
EXtensible Markup Language (XML) has emerged as the dominant standard in describing and exchanging data among heterogeneous data sources. The increasing presence of large volumes of data appearing creates the need to investigate XML Document Warehouses as a means of handling the data. In this paper our focus is twofold. First we utulise Object Oriented (OO) concepts to develop and propose a conceptual design formalism to build meaningful XML Document Warehouses (XDW). This includres: (1) XML (warehouse) repository (xFACT) using OO concepts followed by the transformation of XML Schema constructs and (2) Conceptual Virtual Dimensions (VDims) using Conceptual views (Rajugan, Chang, Dillon and Feng, 2003, 2004). Secondly we address several important outstanding issues related to our proposed design of an XML Document Warehouse.Specifically we note that the xFACT portion is now a complex structure, involving several entities and relationships as opposed to being a simple FACT table as was the case in relational data warehouses, and the notion of Virtual dimensions (VDims) has considerably greater complexity.